GERONTEKNOLOGI BERBASIS KECERDASAN BUDAYA DAN DESAIN BERPUSAT MANUSIA: MEWUJUDKAN KEHIDUPAN LANJUT USIA BERKUALITAS DAN BERMARTABAT - Dony Hermawan, (Journal of Innovation Research and Knowledge, 2026)
The global population aged 60 and over is projected to double to approximately 2.1 billion by 2050, posing unprecedented demographic, economic, and caregiving challenges. Current models focus too much on clinical decline and neglect psychological resilience and cultural belonging, perpetuating fragmented eldercare. This study reconceptualizes aging as a culturally bound human experience, mediated by technology but grounded in dignity. Using a human-centered design framework, Hofstede's dimensions, and Nussbaum's Capacity Approach, the study formulated a model of "Culturally Aware Gerontechnology." The study used mixed methods and involved 220 participants aged 60+ from Indonesia, Japan, and Finland. Quantitative results showed that interfaces incorporating local cultural elements increased technology acceptance by 63% and strengthened psychological resilience by 45%. Qualitative interviews revealed that 74% of older adults preferred technology that supports intergenerational communication over physical assistive devices. The study also revealed low adoption of technology for older adults that is not culturally contextualized. These findings underscore the importance of integrating meaning, ritual, and language into senior technology as a determinant of success. Policy recommendations suggest the need for a Cultural Impact Assessment in the evaluation of senior technology innovations. Innovations based on empathy, culture, and co-creation have been shown to increase social connections, emotional resilience, and community participation in senior living